The postulated innocuity of lifetime exposure to aluminium should be reappraised - Mandriota, Stefano J.; Sappino, André-Pascal (Frontiers in Oncology, 2023)
Because of its chemical versatility and abundance in nature, aluminium is employed in a myriad of frequently used products - including cosmetics and food additives - and applications – drinking water purification procedures being an example. Despite what its widespread use might suggest, aluminium’s harmlessness is not a matter of unanimity in the scientific community. In this article we trace the lines of a growing questioning about the potential mutagenic effects of this metal, due to the data produced over the recent years, and with an eye to the discussions currently underway in this regard between the scientific community, industry, and regulatory bodies.